1992
DOI: 10.1093/jaoac/75.2.307
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Monoclonal Antibody-Based Enzyme-Linked Immunosorbent Assay with Thin-Layer Chromatography and Liquid Chromatography for Aflatoxin B1 Determination in Naturally Contaminated Corn and Mixed Feed

Abstract: A 1-step enzyme-linked Immunosorbent assay (EUSA) method, using a highly sensitive and specific monoclonal antibody to aflatoxin B1 (AFB1), was evaluated by comparison with other methods, Including liquid chromatography (LC) and thinlayer chromatography. The detection limit of the ELISA was as low as 100 pg/assay. AFB1 contents of naturally contaminated corn samples were determined by the 3 methods. The relationships among the methods were Investigated, and good correlations were observed. Mixed feeds were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Successful application of fluorescence enhancers in quantitative analysis has so far been limited to β-CDs, which are thought to act by complexing fluorescent mycotoxins in a hydrophobic hole in the center of the saccharide ring structure (Vazquez et al 1992). CD fluorescence enhancers have been extensively used in quantitative liquid chromatography methods for aflatoxins (Vazquez et al 1991;Hongyo et al 1992;Franco et al 1998;Chiavaro et al 2001), as well as for two other mycotoxins, ochratoxins and zearalenones (Seidel et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Successful application of fluorescence enhancers in quantitative analysis has so far been limited to β-CDs, which are thought to act by complexing fluorescent mycotoxins in a hydrophobic hole in the center of the saccharide ring structure (Vazquez et al 1992). CD fluorescence enhancers have been extensively used in quantitative liquid chromatography methods for aflatoxins (Vazquez et al 1991;Hongyo et al 1992;Franco et al 1998;Chiavaro et al 2001), as well as for two other mycotoxins, ochratoxins and zearalenones (Seidel et al 1993).…”
Section: Resultsmentioning
confidence: 99%
“…Hongyo et al (20) suggested using the same extraction solvent to increase the correlation between ELISA and HPLC methods. In addition, the same extraction procedure allows measuring only the effect of detection variances (37).…”
Section: Resultsmentioning
confidence: 99%
“…The immunological methods that have been used since the 1990s are accepted as official methods for aflatoxin determination in some food commodities; however, it is still necessary to evaluate their efficiency in different foodstuffs and to correlate their results with other accepted analytical methods (19). High-performance liquid chromatog-raphy (HPLC) and enzyme-linked immunosorbent assay (ELISA) methods were found to be highly correlated for the analysis of total aflatoxins in foodstuffs such as peanut, peanut butter, and corn and for aflatoxin B 1 in corn and mixed feeds, whereas in other foodstuffs, such as cereals, low correlations were observed (20). ELISA methods could be used only for screening purposes with the detection limit above the regulatory limits because they are not reliable when used as a quantitative method (21,22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the ubiquitous nature of these fungal species and the constant possibility of their growth and aflatoxin production in various foods and feeds, there has been a concerted effort to develop sensitive aflatoxin assays. Although liquid chromatographic methods are sensitive and accurate, they are expensive, time‐consuming and unsuitable for the analysis of many samples (Hongyo et al . 1992).…”
Section: Introductionmentioning
confidence: 99%